2022
DOI: 10.33369/diksains.2.2.102-108
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Addie Dalam Pengembangan Multimedia Pembelajaran Berbasis Literasi Sains

Abstract: ABSTRAK Pada era perkembangan teknologi dan ilmu pengetahuan, multimedia memegang peran dalam mengakomodasi pembelajaran IPA yang lebih bermakna melalui visualisasi konsep yang abstrrak dan kontektualisasi konsep dalam kehidupan sehari-hari. Penelitian ini bertujuan menganalisis dan menggambarkan tahapan pengembangan multimedia pembelajaran berbasis literasi sains dengan model ADDIE. Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif kualitatif yang menjabarkan penerapan model ADDIE dalam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
16

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 1 publication
0
10
0
16
Order By: Relevance
“…Meanwhile, media experts assessed from a technical point of view, consisting of the cover design and pictures in the Sumbawa folk digital story book "Lalu Dia Lala Jinis". The data and information obtained through the preliminary study were further analyzed to sharpen the basis of the research conducted (Latip, 2022). The results of the analysis based on the results of observations found that the use of folklore books was limited to limited printed textbooks and had not used story books in digital form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, media experts assessed from a technical point of view, consisting of the cover design and pictures in the Sumbawa folk digital story book "Lalu Dia Lala Jinis". The data and information obtained through the preliminary study were further analyzed to sharpen the basis of the research conducted (Latip, 2022). The results of the analysis based on the results of observations found that the use of folklore books was limited to limited printed textbooks and had not used story books in digital form.…”
Section: Resultsmentioning
confidence: 99%
“…The type of research used in this research is Research and Development using the ADDIE model consisting of five stages, namely; 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation which produces a product in the form of a digital storybook learning media for the people of Sumbawa Lalu Dia Lala Jinis (Latip, 2022). Data collection techniques through two stages of activity, namely distributing questionnaires and collecting documentation.…”
Section: Methodsmentioning
confidence: 99%
“…Namun kondisi mental dan emosional siswa yang menjadi bagian utama untuk pengembangan kompetensi justru menjadi yang paling terdampak oleh pandemi. Dampaknya pada proses pembelajaran juga telah banyak ditemukan seperti kondisi emosional siswa (Pranata et al, 2023;Wulandari & Pranata, 2023), kejenuhan dalam pembelajaran (D. H. Putri & Pranata, 2023;Utami et al, 2024), dan minat siswa terus menurun (Harefa et al, 2022). Kondisi ini belum dapat dipastikan telah kembali membaik.…”
Section: Pendahuluanunclassified
“…ADDIE model provides a systematic and adaptive approuch to the design and development of learning activities. Many researchers have used this others with various learning materials [12]. Quartet-based learning development is also widely used using the ADDIE model.…”
Section: The Global Hunger Index In Indonesia In the 2017 Internation...mentioning
confidence: 99%